x-23=7(2x+3)-18

Simple and best practice solution for x-23=7(2x+3)-18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-23=7(2x+3)-18 equation:



x-23=7(2x+3)-18
We move all terms to the left:
x-23-(7(2x+3)-18)=0
We calculate terms in parentheses: -(7(2x+3)-18), so:
7(2x+3)-18
We multiply parentheses
14x+21-18
We add all the numbers together, and all the variables
14x+3
Back to the equation:
-(14x+3)
We get rid of parentheses
x-14x-3-23=0
We add all the numbers together, and all the variables
-13x-26=0
We move all terms containing x to the left, all other terms to the right
-13x=26
x=26/-13
x=-2

See similar equations:

| d3− 1=1 | | 4n-16=8n-4 | | 2+1/3t=1+1/45 | | b+2=2b-4 | | 6x-(4x-5)=31 | | w-1.9=9.5 | | (3a-10)(2a-7)=0 | | 384=x(480) | | 2+1/3=1+1/4t | | x(1/3x)=108 | | −4y−5(8y−9)=−6−9(4−y) | | 2(x-1)=-5x-30 | | -x–74=-1 | | -10+5x+10x+-5=180 | | 3/5n=60 | | 8v+38=-9(v-8) | | 30=1+4y+9+14 | | -10+5x+10+-5=180 | | 3(y-4)=6y-33 | | ½(6x+10)+2=–20 | | 3y+2y+10=20 | | -8=-5+3y | | −7(−5d−1)−3d=139−d | | 3c=5=30 | | 4-7x=12+2x | | x²–9x+20=2 | | 5v-6v=2 | | 8(2x+1)=8+16x | | 5/x-6=3x+2 | | 12b+9=12b-11 | | 4(3x+5)=12x+15 | | 5x-3+x+25=176 |

Equations solver categories